Predictors of incident malnutrition in older Irish adults from The Irish Longitudinal Study on Ageing (TILDA) cohort- a MaNuEL study. - Laird, Eamon; Kenny, Rose; O'Connor, Deirdre (My University, 2018)
Older adults are at increased risk of malnutrition, which is associated with poorer health, quality of life, and worse disease outcomes. This study identifies predictors of incident malnutrition using data from a subsample (n = 1,841) of The Irish Longitudinal Study on Ageing. Participants were excluded if they were less than 65 years, missing body mass index data at baseline or follow-up, missing baseline weight loss data or malnourished at baseline (body mass index <20 kg/m2 or unplanned weight loss ≥4.5 kg in the previous year). Logistic regression analysis was performed with incident malnutrition (body mass index <20 kg/m2 and/or calculated weight loss >10% over follow-up) as the dependent variable. Factors showing significant (p < .05) univariate associations with incident malnutrition were entered into a multivariate model. The analysis was then repeated, stratified by sex. The 2-year incidence of malnutrition was 10.7%. Unmarried/separated/divorced status (vs married but not widowed), hospitalization in the previous year, difficulties walking 100 m, or climbing stairs independently predicted incident malnutrition at follow-up. When examined by sex, hospitalization in the previous year, falls during follow-up, and self-reported difficulties climbing stairs predicted malnutrition in males. Receiving social support and cognitive impairment predicted malnutrition in females. The development of malnutrition has a range of predictors. These can be assessed using simple questions to identify vulnerable persons.
PUBLISHED
Keywords: Community-dwelling, Protein–energy malnutrition, Undernutrition; Ageing